Efeito do co2 sobre a qualidade nutricional, ferrugem e fusariose da alfafa - Santos, Michelli De Souza dos [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
The atmospheric CO2 concentration, the main gas responsible for intensifying the greenhouse effect, has increased significantly in recent decades. Alfalfa is important forage that can have its characteristics altered by increased atmospheric CO2 concentration, facilitating the occurrence of diseases and enhancing the emission of greenhouse gases after its ingestion by animals. Given this scenario, the objective of this study was to assess the impact of increased CO2 concentration in the air on alfalfa diseases, plant growth and chemical composition. Assays were performed in the field with direct seeding of alfalfa seed cultivar Creole in open top chambers (OTC), adopting the trial randomized block design with three replications. The treatments were: control without OTC, with the concentration of 390 μmol mol-1 of CO2; OTC without CO2 injection with 400 μmol mol-1 of CO2; and OTC injected CO2 with target concentration of 500 μmol mol-1. In the shoots, analyzes were performed to determine dry matter, ash, organic matter, nitrogen in neutral detergent fiber (NDF-N), nitrogen in acid detergent fiber (ADF-N), crude protein and lignin and foliar analysis. In addition to these measures of plant height, stem length and root weight of biomass of the root and shoot and inflorescence. One disease was evaluated during the second trials: rust, caused by Uromyces striatus and one were evaluated during the two last trials: the wilt of fusarium caused by Fusarium oxysporum f. sp. medicaginis. The diseases severity was assessed weekly by notes during 28 days. The defoliation caused by rust was evaluated by the percentage of leaves. Height of stems, the relationship between the length of stem and root, biomass of roots and shoots were higher in the treatment with CO2 injection. Dry matter, ash, organic matter, n- NDF, ADF-n, crude protein and lignin showed no statistical difference between the treatments. The rust ...

A concentração atmosférica de CO2, principal gás responsável pela intensificação do efeito estufa, vem aumentando significativamente nas últimas décadas. A alfafa é uma importante forrageira que pode ter suas características alteradas pelo aumento da concentração de CO2 atmosférico, favorecendo a ocorrência de doenças e intensificando a emissão de gases de efeito estufa após sua ingestão por animais. Diante desse cenário, o objetivo desse trabalho foi verificar o impacto do aumento da concentração de CO2 do ar em doenças da alfafa, crescimento das plantas e composição bromatológica. Os ensaios foram realizados em campo, com semeadura direta de sementes de alfafa da cultivar crioula em estufas de topo aberto (OTC), adotando o delineamento experimental em blocos casualizados, com três repetições. Os tratamentos foram: testemunha sem OTC, com a concentração de 390 μmol mol-1 de CO2; OTC sem injeção de CO2, com 400 μmol mol-1 de CO2; e OTC com injeção de CO2 até atingir 500 μmol mol-1 de CO2. Na parte aérea das plantas, foram realizadas análises para determinar a matéria seca, matéria mineral, matéria orgânica, nitrogênio em fibra detergente neutro (n-FDN), nitrogênio em fibra detergente ácido (n-FDA), proteína bruta e lignina e análise química foliar. Além dessas, foram realizadas medidas da altura das plantas, relação entre o comprimento da haste e da raiz, peso da biomassa da raiz e da parte aérea e a contagem das inflorescências. Uma doença foi avaliada nos dois primeiros ensaios: a ferrugem, causada por Uromyces striatus, e a segunda foi avaliada nos dois últimos ensaios: murcha de fusário, causada por Fusarium oxysporum f. sp. medicaginis. A severidade das doenças foi avaliada por meio de notas, semanalmente, durante 28 dias ...
Effect of co2 on nutrition quality, and rust fusariose of alfalfa
Keywords: Fusario; Alfafa - Doenças e pragas; Mudanças climáticas; Fusarium